Highly selective etherification of fructose and 5‐hydroxymethylfurfural over a novel Pd‐Ru/MXene catalyst for sustainable liquid fuel production. (3rd May 2021) - Bharath, Govindan; Rambabu, Krishnamoorthy; Hai, Abdul; Morajkar, Pranay P.; Salkar, Akshay V.; Hasan, Shadi W.; Show, Pau Loke; Banat, Fawzi
Summary: Sustainable liquid fuel production from bio‐oil compounds has attracted considerable attention in recent years. The catalytic etherification of 5‐hydroxymethylfurfural (HMF) to ethoxymethylfurfural (EMF) is an effective approach for the production of liquid fuels. However, the development of high‐performance and chemically stable catalysts has remained challenging. In this work, ultra‐small Pd‐Ru NPs were successfully immobilized on the surfaces of 2D MXene nanosheets (Pd‐Ru/MXene) via fish sperm DNA‐assisted microwave process. HR‐TEM imaging results with SAED analysis showed that the hexagonal closed‐pack (hcp) Pd‐Ru NPs were grown on the surfaces of sheet‐like MXene, thus enhancing the specific surface area of 117 m 2  g −1 and providing a higher density of the acid‐base sites. Furthermore, Pd‐Ru/MXene was employed for the etherification of HMF into EMF. The results showed that the Pd‐Ru/MXene catalyst exhibited 98% EMF yield and 100% HMF conversion with the prolonged usage of catalyst for five consecutive reuse cycles. Additionally, fructose was directly converted into EMF with a higher yield of 82% over the Pd‐Ru/MXene catalyst at lower reaction conditions. The recyclability test of the used Pd‐Ru/MXene catalyst demonstrated its chemical stability under prolonged usage for several hours and is therefore suitable for commercial renewable liquid fuel production. Novelty Statement: The catalytic transformation of biomass into diesel‐miscible biofuel is a sustainable route for liquid fuel production and has recently attracted massive attention. The chemically stable and high‐performance Pd‐Ru/MXene catalyst was successfully prepared and characterized. The study demonstrated that the Pd‐Ru/MXene catalyst exhibits superior catalytic activity toward the direct conversion of fructose and 5‐hydroxymethylfurfural (5‐HMF) into 5‐ethoxymethylfurfural (5‐EMF), which is a promising conversion method for the production of biofuels from biomass. Abstract : A highly stable Pd‐Ru/MXene nanocatalyst was successfully prepared via microwave irradiation. The obtained catalyst was used as high performing catalyst for etherification of fructose and 5‐hydroxymethylfurfural (5‐HMF) to ethoxymethylfurfural (EMF). The Pd‐Ru/MXene nanocatalyst exhibited higher EMF yield at 100% 5‐HMF conversion and chemically stable for several recycles. Hence, Pd‐Ru/MXene nanocatalyst is suitable for commercial applications.